Penyembuhan Luka Perineum Menggunakan Air Rebusan Daun Sirih Pada Pasien Post Partum - Nurchella, Sagita Indah; Sulistyowati, Priyatin; Suciliyana, Yolinda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The maternal mortality rate in Central Java Province was 64.18% during childbirth. Purbalingga Regency contributed 12 or 34.6% of cases of maternal death in 2019 and 7 of them were caused by bleeding. The cause of post partum bleeding is 20% due to trauma such as perineal lacerations. The existence of a wound in the perineum can cause infection and pain for several weeks after giving birth. Perineal wound care aims to reduce infection and the most important thing is to accelerate wound healing. The anti-inflammatory content of betel leaves can help speed up the healing process of perineal wounds. The purpose of this study is to describe "Acceleration of Perineal Wound Healing by Administering Betel Leaf Water Decoction to Post Partum Patients in the Work Area of the Kalikajar Purbalingga Health Center". The methods used in this research are observation, direct interviews and documentation. The results obtained in this study were that the implementation of perineal care using betel leaf boiled water which was used routinely in the morning and evening for 4 days was able to speed up the healing of perineal wounds and the genital area looked rougher. The conclusion is that there is a significant effect in accelerating perineal wound healing by using betel leaf boiled water.